Menggagas Ontologi Ilmu Keislaman - Komaru Zaman (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Ontology as a science or theory about the existence of existing nature.The object of science or science is an empirical world, namely the world that can be reached by the five senses and the object of science is a sensory experience, learning about the nature of something tangible based on logic alone.From this theory of fact (ontology) then gave rise to several traditions in philosophy, among others: Philosophy of Materialism, Philosophy of Idealism, Philosophy of Dualism, Philosophy of Skepticism and Philosophy of Agnoticism.Adaya ontology that if associated with Islamic science of course this theory seeks to create a new formulation that can provide answers to some problems in accordance with the context.